Cultural influences on national rates of innovation - Shane, Scott (Journal of Business Venturing, 1993)
The purpose of this research was to examine the effect of the cultural values of individualism, power distance, uncertainty avoidance, and masculinity on national rates of innovation in 33 countries in 1975 and 1980. The study found that rates of innovation are most closely associated with the cultural value of uncertainty acceptance, but that lack of power distance and individualism also are related to high rates of innovation. This research suggests that nations may differ in their rates of innovation because of the cultural values of their citizens. These findings have important implications for managers and policy-makers. First, culture matters. Countries may not be able to increase their rates of innovation simply by increasing the amount of money spent on research and development or industrial infrastructure. They also may need to change the values of their citizens to those that encourage innovative activity. This concept, in turn, suggests that national rates of innovation are driven by more fundamental forces than economic conditions, and that societal change may be necessary to make less innovative societies more innovative. Second, the values associated with high national rates of innovation are those that many scholars have long argued are important at the firm level. An acceptance of uncertainty appears to be necessary, probably because innovation requires a tolerance for risk and change. Individualism seems to be important, perhaps because of its association with autonomy, independence, and freedom. Lack of power distance appears important, perhaps reflecting the role that tolerance of change in the social order and distribution of power play in the innovation process. Third, the study indicates that the strength of the relationship between innovation and two cultural values—individualism and lack of power distance—were stronger in 1975 than in 1980, suggesting, perhaps, that these values are becoming less important in spurring the innovation process. This finding supports the anecdotal evidence that many collectivist and hierarchical Asian nations are becoming more innovative. Fourth, this study shows that per capita income is a more important economic variable than industrial structure in determining national rates of innovation. This finding confirms previous work that has shown that as nations become wealthier, they become more innovative. The reason may be that wealthier countries have more demand for innovations, both because innovations are often laborsaving, and because wealthier nations have greater demand for new and differentiated consumer goods.